Reforming agricultural support policy for transforming agrifood systems: China and Global Food Policy Report 2022 - China Agricultural University; Zhejiang University; Nanjing Agricultural University; Chinese Academy of Agricultural Sciences; International Food Policy Research Institute (China Agricultural University, 2022)
Remarkable achievements in global food security have been made in the past several decades. Food production has grown significantly and outpaced the population growth. Household food consumption has increased, and undernourishment has declined dramatically. However, due to multiple risks and threats such as climate change, COVID-19, environmental degradation, trade frictions, and regional conflicts, global food security and nutrition face unprecedented challenges. In fact, the number of hungry people in the world has been increasing since 2015, with more than 800 million people now suffering from hunger. After decades of development, China has ended hunger. In the new development stage, the Chinese government has proposed even higher development goals; these include Healthy China 2030, Rural Revitalization, Ecological Civilization, Common Prosperity and Carbon Neutrality.